The implications of digital communication between parents and teachers from a teachers’ point of view - Khoo, Nur Aini Khoo binti Ahmad Fuad; Osman, Sharifah; Daud, Mohd Fadzil; Kumar, Jeya Amantha; Kurniati, Dian (Humanities, Arts and Social Sciences Studies, 2024)
Digital communication has been popular among general Malaysian users. It comes as no surprise that digital communication is taking over in educational settings. Parent-teacher communication is very important, because both parties play a big role in children’s learning wellbeing. Thus, this study explores the advantages and disadvantages of using WhatsApp groups as a digital communication tool for parent-teacher communication. Because WhatsApp groups are not yet considered a formal medium, there are no rules or regulations in place to govern communication. Therefore, this study aims to guide teachers on managing digital communication between parents and teachers so that the alternative can be utilised efficiently. This qualitative study involved six teacher informants responsible as class teachers for any grades or levels in national and government primary and secondary schools located around Johor Bahru. Data were collected using semi-structured interviews and were analysed using thematic analysis. Based on the findings, there are both advantages and disadvantages to using WhatsApp groups among parents and teachers. WhatsApp groups offer benefits such as information being delivered easily and quickly; parents and teachers accessing information in WhatsApp groups from various locations; and immediate interaction between parents and teachers. The conveniences that WhatsApp group functions offer can foster cooperation between parents and teachers. However, there are several disadvantages to using WhatsApp groups that are the unintentional extension of teachers’ working hours caused by the flexibility of WhatsApp groups, an invasion of teachers’ privacy and its contribution to any discussions on trivial matters. WhatsApp groups should set rules and restrictions to improve the groups’ effectiveness and efficiency for parents and teachers. Teachers should serve as the group’s host and administrator in order to preserve the semi-formal relationships between parents and teachers. Because teachers’ healthy work-life balance is also important, establishing good practice for managing WhatsApp groups is essential.